(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
The paper investigates the relations between perception and language in Maurice Merleau-Ponty’s philosophy in the light of the recent publications of the course notes dating back to the early fifties, Le monde sensible et le monde de l’expression and Recherches sur l’usage littéraire du langage. The first course gives us an articulated conception of expression, which plays a decisive role in explaining the continuity between perception and language. Perception is closely associated with linguistic acts of parole and sharing an expressive, diacritical structure analogous to the one characterizing linguistic meanings. Nonetheless some philosophical problems regarding Merleau-Ponty’s basically phenomenological method of searching for the roots of linguistic meanings in perceptions are considered. In the second course the idea of the two alleged languages finds support and is developed in a more radical direction through Merleau-Ponty’s engagement with the experience of the writer trying to find new words to convey his own experience of the word. This emphasis on the langage conquérant at the expenses of ordinary shared linguistic practices is critically considered, also in the light of other research trajectories followed by the French philosopher in the same period.